PRO-ENVIRONMENTAL BEHAVIOR AND RECYCLING: LITERATURE REVIEW AND POLICY CONSIDERATIONS - CHIERRITO-ARRUDA,EDUARDO (2018)
Abstract The environmental scenario requires the participation of the society in the integration of individual responsibilities to the political action. The recycling pro-environmental behavior contributes to the proper disposal of solid waste, a major challenge in urban public management. The article aims to analyze the scientific production of the pro-environmental behaviors and recycling in order to weave notes that promote behavioral changes provided for in public policies. The PsycINFO, Scielo and EBSCOhost databases were consulted using the keywords: environmental attitudes, pro-environmental behavior and recycling. We selected 51 articles, among which predominated the investigation into motivation to recycle behavior, influence of social network and social norms. Environmental attitudes and behavior to recycle have shown to be related to social norms, motivation, identity, altruism and awareness; these should be considered when planning public policies and environmental awareness actions.